The kite runner - Abdalla, Khalid; Horberg, William; Parkes, Walter F.; Yeldham, Rebecca; Walsh, E. Bennett; Benioff, David; Forster, Marc, 1969-; Ershadi, Homayoun; Toub, Shaun; Leoni, Atossa; Taghmaoui, Sad̐.; Ebrahibi, Zekiria; et al. (Universal City, Calif. : DreamWorks Home Entertainment, 2007)
In a divided country on the verge of war, two childhood friends, Amir and Hassan, are about to be torn apart forever. It's a glorious afternoon in Kabul and the skies are bursting with the exhilarating joy of a kite-fighting tournament. But in the aftermath of the day's victory, one boy's fearful act of betrayal will mark their lives forever and set in motion an epic quest for redemption. Now, after 20 years of living in America, Amir returns to a perilous Afghanistan under the Taliban's iron-fisted rule to face the secrets that still haunt him and take one last daring chance to set things right.
Title from container.
Widescreen.
Based on the book by Khaled Hosseini.
Originally released as a motion picture in 2007.
Special features: Commentary with Marc Forster, Khalid Hosseini and David Benioff; words from The kite runner; images from The kite runner; theatrical trailer.
Director of photography, Roberto Schaefer ; editor, Matt Cheese ; music, Alberto Iglesias ; costume designer, Frank L. Fleming ; production designer, Carlos Conti.
Keywords: Kites -- Afghanistan -- Drama; Secrecy -- Drama; Betrayal -- Afghanistan -- Drama; Friendship -- Drama; Afghanistan -- Drama; Foreign language films; Films for the hearing impaired; Feature films; Suspense films